A teoria da complexidade como referencial epistemológico na pesquisa em política educacional no Brasil: análise sobre o estado atual e seu potencial interpretativo para os estudos do campo - Carvalho, Roberta Cajaseiras de (2019)
The purpose of this research was to analyze the use of Complexity Theory as an epistemological reference and its interpretive potential in educational policy research in Brazil, and it was characterized by the basic nature and qualitative approach. The research problem that guided the research was: “Is complexity theory used as an epistemological reference in educational policy research in Brazil?”. This thesis is linked to the line of educacional policy research, and anchored in the Approach of the Epistemologies of Educational Policy (EEPE), identifies itself with the same as follows: regarding the epistemological perspective, anchors in the historical-rationalist worldview of Gastón Bachelard (1978; 1985); as to the epistemological position, assumes the Theory of Complexity from the proposal of Edgar Morin; and on the epistemetodological approach, is based on meta-research (TELLO; MAINARDES, 2015), supported by the deductive-analytic method and the content analysis (Bardin, 2016). The main theoretical references used in the construction and approach of the research problem were Morin (2000b, 2000a, 2008, 2010), Le Moigne (2000a, 2000b, 2000c), Capra (2014), Bertalanffy (2015), Snyder (2013) and Almeida (2014a, 2014b). The meta-analysis analyzed 47 articles published between 2014 and 2018 in scientific journals in the field of educational policy in Brazil, where it was identified that only a small part of the corpus (7,8%) used the theory of complexity as an epistemological reference, demonstrating that the rational understanding of complex systems is not yet common in educational policy studies of the corpus. The analysis of texts that have the theory of complexity as an epistemological reference reinforced the importance of the union between empirical analysis and rationality, and emphasized the importance of pluralism for the theoretical foundation. As for the analysis of the potential of complexity theory as a theoretical reference and world view, it was possible to infer that it is adequate for studies in the field of educational policy, as it offers an analytical alternative to the traditional field references. As to the role of complexity as a reference for methodological organization of research, this research has identified that complex modeling is appropriate to studies in educational policy, allowing many of the complex principles to be applied in an empirical way, promoting applied Rationalism in action. As a challenge for the field, it is proposed: an effort to build more plural research groups and promote transdisciplinarity; the need to assume that computer models are important tools for deep and continuous analysis of complex systems; conduc ting further research on network analysis and on the use of agent-based modeling (ABM) in the field of educational policy; the accomplishment of more meta -surveys, to analyze the insertion of the theme 'educational policies' in investigations conducted by other fields of knowledge.